National Identity and Perceived Discrimination Predict Changes in Ethnic Identity Commitment: Evidence from a Longitudinal Study of Latino College Students. Issue 3 (16th February 2012) - Fuller‐Rowell, Thomas E.; Ong, Anthony D.; Phinney, Jean S.
Abstract : The current study tests the hypothesis that the influence of perceived discrimination on ethnic identity commitment is moderated by national identity (a person's psychological affiliation to their country of residence). A positive direct effect of national identity on ethnic identity commitment was also predicted. Analyses are based on a sample of Latino college students in the United States followed across eight consecutive semesters ( N = 97; M age = 18). In support of the hypotheses, a significant interaction was found between discrimination and national identity. In particular, perceived discrimination in the first year of college was positively associated with changes in ethnic identity commitment across the college years among participants with a weaker national identity, but negatively associated with changes in ethnic identity commitment among participants with a stronger national identity. Higher levels of national identity were also associated with greater increases in ethnic identity commitment over time.